The perceived critical sustainability dimensions of ecotourism among human ecology students - Carpio, Arantxa Alex (Journal of Human Ecology, 2019)
Sustainability is a critical concept discussed in the courses offered by the College of Human Ecolo- gy, University of the Philippines Los Baños. One critical sustainability industry reviewed is ecotour- ism, which emerged as a reaction to the negative impacts and limitations of conventional tourism. The youth is a critical sector in ecotourism due to their greater access to travel and the increasing discourse on sustainability. This study was conducted to identify the key sustainability dimensions that the youth, specifically Human Ecology students, perceive as critical to ecotourism. The study employed a survey research with 87 out of 219 HUME 100 students during the first semester of AY 2018-2019. The five sustainability dimensions assessed in terms of their importance to ecotourism are (1) economic, (2) cultural, (3) social, (4) environmental, and (5) institutional. Respondents viewed most sustainability indicators as “important” to “very important”. Using multiple regression analysis, factors identified as significant based on students’ ratings per sustainability dimension were (1) age and familiarity with ecotourism (environmental), (2) degree program and senior high school strand (economic), (3) sex for both (social and institutional), and (4) awareness of the difference between tourism and ecotourism (cultural). MANOVA results showed that the sex of respondents is a signifi- cant factor for the environmental, social, and institutional sustainability dimensions. Study results are useful baseline information on the critical sustainability dimensions of ecotourism from the perspec- tive of Human Ecology students and could serve as inputs in planning and promoting ecotourism initiatives targeting the youth.